2020
DOI: 10.1371/journal.pone.0241187
|View full text |Cite
|
Sign up to set email alerts
|

Children with congenital heart disease exhibit seasonal variation in physical activity

Abstract: Objective We sought to identify seasonal variation in physical activity that different physical activity measurement tools can capture in children with congenital heart disease. Methods Data were collected as part of a prospective cohort study at BC Children’s Hospital, Vancouver, Canada. Daily step counts of children aged 9–16 years with moderate-to-severe CHD were assessed continuously for 1-year via a commercial activity tracker (Fitbit Charge 2™). Physical activity levels were also assessed conventionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…One study further claimed there are no adverse effects of Fitbit devices ( 32 ). Nine of 25 studies contrarily discussed disadvantages of Fitbit devices, including not being designed for children ( 38 ), being difficult to use ( 39 , 40 ), causing rash and eczema ( 40 ), falling off during exercise ( 41 ), having limited data collection abilities ( 30 , 37 , 42 ), and having a likelihood of non-compliance in adolescents ( 30 , 33 ) ( Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study further claimed there are no adverse effects of Fitbit devices ( 32 ). Nine of 25 studies contrarily discussed disadvantages of Fitbit devices, including not being designed for children ( 38 ), being difficult to use ( 39 , 40 ), causing rash and eczema ( 40 ), falling off during exercise ( 41 ), having limited data collection abilities ( 30 , 37 , 42 ), and having a likelihood of non-compliance in adolescents ( 30 , 33 ) ( Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that consumer PATs, such as those manufactured by Fitbit, Garmin and Jawbone are worn by rehabilitation subjects to capture the outcome of physical activity [13,23,37,38]. However, since these devices use step counts and estimated energy expenditure as the main outcomes, one could conjecture that the physical activity consists only of walking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the wristband-type consumer PATs are not practical for comparative assessment with others, but that they can be used for capturing changes within the user [38][39][40]. It is known that if appropriate support is not provided to the patient population undergoing rehabilitation, mortality and the degree of long-term care may worsen due to a decrease in physical activity and disrupted sleep cycle, leading to irregular daytime sleeping [3,4,41].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, reduced physical activity levels observed during summer vacation are followed by increased physical activity when students return to school. 25 , 26 Schools are well known to provide opportunities and facilities for physical activity through physical education class, recess, and structured sport teams. 27 , 28 Our data suggest that despite the prior beneficial effect of school on physical activity participation, the extended period of inactivity since March 2020 due to COVID-19 related restrictions may have adversely affected physical activity behaviour in children with CHD upon resumption of school.…”
Section: Discussionmentioning
confidence: 99%